Peran Pendidikan Agama Kristen Dalam Pembentukan Iman Kepada Anak Di Jemaat Gereja Bethel Injil Sepenuh Yerusalem Baru, Surabaya Berdasarkan Kitab Ulangan 6:4-9: The Role of Christian Religious Education in Shaping Children’s Faith in the Congregation of Bethel Full Gospel Church “Yerusalem Baru,” Surabaya, Based on Deuteronomy 6:4–9 - Eko Basuki; Liantoro Liantoro; Dunant Frederick Saukotta; Metalia Margaret (Journal of Religious and Socio-Cultural, 2024)
Deuteronomy 6:4-9, also known as the Shema, provides a strong foundation for the formation of Christian faith. In the context of the church, Christian Education teaching can be implemented through several relevant and effective approaches. Christian Education teachers can guide children in understanding and internalizing the fundamental teachings of the oneness of God, love and obedience to Him, and the importance of keeping His commandments. This approach allows children to deeply understand the basic teachings of the Christian faith. The purpose of this study is the application of the values ​​contained in Deuteronomy 6:4-9 in everyday life, Christian Education teachers can help children understand the relevance and practical application of these teachings in the context of their lives. This can be done through stories, illustrations, and concrete examples that illustrate how these values ​​can be lived and practiced in various life situations. By actively involving parents and the church community, children can be placed in an environment that strengthens the values ​​of faith taught in Deuteronomy 6:4-9. Through the implementation of holistic PAK teaching integrated with the teachings of Deuteronomy 6:4-9, it is hoped that the younger generation in the congregation of the New Jerusalem Bethel Gospel Church, Surabaya, can grow in strong faith and be able to face spiritual challenges in their lives. Kitab Ulangan 6:4-9, yang juga dikenal sebagai Syema, memberikan dasar yang kuat bagi pembentukan iman Kristen. Dalam konteks gereja tersebut, pengajaran PAK dapat diimplementasikan melalui beberapa pendekatan yang relevan dan efektif. Guru PAK dapat membimbing anak-anak dalam memahami dan menginternalisasi ajaran fundamental tentang keesaan Allah, cinta dan ketaatan kepada-Nya, serta pentingnya memelihara perintah-Nya. Pendekatan ini memungkinkan anak-anak untuk memahami secara mendalam ajaran-ajaran dasar dalam iman Kristen. Tujuan dari penelitian ini adalah penerapan nilai-nilai yang terkandung dalam Kitab Ulangan 6:4-9 dalam kehidupan sehari-hari, para guru PAK dapat membantu anak-anak dalam memahami relevansi dan aplikasi praktis dari ajaran tersebut dalam konteks kehidupan mereka. Ini dapat dilakukan melalui cerita, ilustrasi, dan contoh konkret yang menggambarkan bagaimana nilai-nilai tersebut dapat dihayati dan diamalkan dalam berbagai situasi kehidupan. Dengan melibatkan orang tua dan komunitas gereja secara aktif, anak-anak dapat ditempatkan dalam lingkungan yang memperkuat nilai-nilai iman yang diajarkan dalam Kitab Ulangan 6:4-9. Melalui implementasi pengajaran PAK yang holistik dan terintegrasi dengan ajaran Kitab Ulangan 6:4-9, diharapkan generasi muda dalam jemaat Gereja Bethel Injil Sepenuh Yerusalem Baru, Surabaya, dapat tumbuh dalam iman yang kokoh dan mampu menghadapi tantangan spiritual dalam kehidupan mereka.